Secondary primary malignancies after treatment with chemo-immunotherapy in treatment-naïve patients with CLL: a systematic literature review. Issue 3 (4th March 2022) - Csanádi, Marcell; Ágh, Tamás; Tordai, Attila; Tapprich, Christoph; Vokó, Zoltán; Stamatopoulos, Kostas
ABSTRACT: Objectives: In chronic lymphocytic leukemia (CLL), therapy-related cytotoxicity and the resulting immunodeficiency are thought to contribute to the development of secondary primary malignancies (SPM). Here, we analyzed clinical trial data on the occurrence of SPM following chemo-immunotherapy (CIT) regimens in treatment-naïve CLL patients. Methods: A systematic literature search was conducted covering multiple databases between 2003 and 2019. Data from relevant clinical trials on the proportion of patients with SPMs were extracted. Then, the number of SPM patients/person-years was calculated by taking into account the trials' follow-up time. Finally, a random-effects meta-analysis to pool the rates from individual studies was performed. Results: We identified 22 studies reporting SPM data available for analysis. Random-effects meta-analysis estimated that the number of SPM patients/1000 person-years was 24 (95%CI: 19–29). Results from trials with cancer-specific data indicated 19 (95%CI: 14–26) solid and 9 (95%CI: 6–12) hematological SPM patients/1000 person-years. These estimations did not change significantly when sub-groups were analyzed by CIT regimens. Conclusion: Although pooling data with the intention to analyze adverse event rates is challenging, our study concluded that for CIT regimens, SPM should be considered an important adverse outcome. Different regimens showed similar trends; however, other clinical and demographic factors also have profound impact.